(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
Establishing an effective system for training tour guides is a basic condition for developing the tourism sector. Therefore, the study aimed to clarify the importance of the tour guide in the tourism industry, identify the role of training the tour guide in raising his skills, areas of training, explore the basic skills of the tour guide, and measure the impact of training on developing the skills of the tour guide in the Iraqi tourism sector. The study used the descriptive analytical approach and the survey approach by distributing the electronic questionnaire form to a facilitated sample of workers in the Iraqi Tourism Authority. Its strength was (35) individuals. The results of the study concluded that there is a statistically significant impact of training on developing the skills of the tour guide in the Iraqi tourism sector. The study recommended regular training of tour guides to enable them to update information and become familiar with modern means of tour guidance.